2012
DOI: 10.1007/s11552-012-9402-8
|View full text |Cite
|
Sign up to set email alerts
|

Management of Digital Tendon Avulsion at the Musculotendinous Junction of the Forearm: A Systematic Review

Abstract: In the management of tendon avulsions at the musculotendinous junction, specific procedures are favored depending on the mechanism of injury, the type of tendon and digit involved, and the level of bone amputation. An algorithm is presented to facilitate optimal treatment based on these injury characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 31 publications
(56 reference statements)
0
20
0
1
Order By: Relevance
“…If serious damage is suspected in the examination, an immediate exploration could provide the chance to reconnect the two ends of a broken structure, with no additional dissection needed to expose and use other tendons [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If serious damage is suspected in the examination, an immediate exploration could provide the chance to reconnect the two ends of a broken structure, with no additional dissection needed to expose and use other tendons [8].…”
Section: Discussionmentioning
confidence: 99%
“…Boyes et al [7] investigated 80 subcutaneous ruptures of the flexor tendons and reported that avulsion at the tendon insertion accounted for 62.8% of the studied cases, whereas avulsions at the MTJ accounted for only 5.1%. Although uncommon, tendon avulsion injuries at the MTJ could not be overlooked because treatment failures could result in an unrecognised compartment syndrome on a short-term basis when the tendons are avulsed from their muscle belly on the forearm or lumbricals on the hand, or in significant disability on a longterm basis [8]. Although methods of conservative management, such as splinting or wearing a brace, have occasionally been reported, most of the reported series involved cases of patients who underwent surgery or who had ruptures involv-ing the tendons [7,[9][10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…
AbstractClosed traumatic rupture of tendons at the musculotendinous junction occurs when there is a sudden longitudinal pull of the tendon against a contracting muscle as in resisted extension or flexion of a finger [1]. The weakest point in the whole musculotendinous unit is however at the distal insertion point of the tendon into bone as described by Boyes [2].
…”
mentioning
confidence: 99%